TANGGUNGJAWAB HUKUM DOKTER TERHADAP PASIEN DI KAMAR BEDAH - Arifin, Jajang (Universitas Wiralodra, 2022)
The relationship between doctors and patients has been going on for a long time. A doctoris considered to be someone who gives treatment to people who need it. The legalrelationship between doctors and patients begins with a paternalistic vertical relationshippattern like father and son which departs from the principle of